Screening for “window-period” acute HIV infection among pregnant women in rural South Africa - Kharsany, ABM (2010)
OBJECTIVE: To evaluate HIV-1 RNA pooled nucleic acid amplification testing (NAAT) strategy to screen pregnant women in the “window period” of acute HIV infection (AHI) in rural South Africa. METHODS: In 2007 and 2008, 750 consecutive pregnant women at their first prenatal care visit to primary health care clinics were tested anonymously for HIV infection. HIV-1 RNA pooled NAAT was performed on HIV antibody negative samples. All positive pools were tested individually and positive samples were classified as incident cases to calculate HIV incidence. RESULTS: The overall HIV prevalence was 37.3% [95% confidence interval (CI) 34.3–41.3]. Of the 467 HIV antibody negative samples, four (0.9%) were HIV-1 RNA positive. The mean viral copies/ml in the four samples was 386260 (range 64 200 to 1228130). The HIV incidence was 11.2% per year (95% CI 0.3–22.1) and all women with AHI were ≤ 21 years of age. CONCLUSIONS: Identifying AHI in pregnancy is important for health interventions to reduce perinatal and heterosexual transmission of HIV; and to estimate HIV incidence for epidemiological surveillance.